1990
DOI: 10.1073/pnas.87.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of L-leucyl-L-leucine methyl ester-mediated killing of cytotoxic lymphocytes: dependence on a lysosomal thiol protease, dipeptidyl peptidase I, that is enriched in these cells.

Abstract: Exposure ofmurine or human lymphocytes to L-leucyl-L-leucine methyl ester (Leu-Leu-OMe) results in selective killing of cytotoxic lymphocytes, whereas helper T cells and B cells remain functionally intact. Cytolytic lymphocytes incubated in the presence of toxic concentrations of Leu-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
154
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(161 citation statements)
references
References 24 publications
7
154
0
Order By: Relevance
“…To analyze the CA-074-Me block of necrotic cell death, we challenged primary murine macrophages with lysosome-destabilizing agents and pyroptosis inducers in the presence of increasing CA-074-Me concentrations. As a model agent for lysosome-mediated necrosis we used the soluble dipeptide methyl ester LLOMe, 28,50,51 and as prototypical pyroptosis inducers we used anthrax lethal toxin (LT) and LPS/nigericin. 8,9,25,40 We found that 10 mM CA-074-Me was sufficient to block LLOMe killing, while 50 mM CA-074-Me was required to block pyroptotic cell death mediated by LPS/nigericin and LT (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To analyze the CA-074-Me block of necrotic cell death, we challenged primary murine macrophages with lysosome-destabilizing agents and pyroptosis inducers in the presence of increasing CA-074-Me concentrations. As a model agent for lysosome-mediated necrosis we used the soluble dipeptide methyl ester LLOMe, 28,50,51 and as prototypical pyroptosis inducers we used anthrax lethal toxin (LT) and LPS/nigericin. 8,9,25,40 We found that 10 mM CA-074-Me was sufficient to block LLOMe killing, while 50 mM CA-074-Me was required to block pyroptotic cell death mediated by LPS/nigericin and LT (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a diverse range of substances, such as silica, bacterial/ viral toxins, and β-amyloid, can all impair lysosomal membranes in vivo. Thus, we next examined the behavior of FBXO27 following disruption of lysosomal membranes using the lysosomotropic compound L-leucyl-L-leucine methyl ester (LLOMe) (19). To monitor lysosome rupture, we used cells that express GFPgalectin3 (GFP-Gal3) (16).…”
Section: Membrane Targeting and Glycoprotein Binding Activity Of Fbxo27mentioning
confidence: 99%
“…Early examples of lysosomotropic detergents were amines with hydrophobic side-chains, such as imidazole or morpholine (Miller et al, 1983), although it is not completely clear whether they disrupt lysosomal membranes only or also plasmalemma, and whether this is cell type-dependent. However, the best characterized lysosomotropic detergent is L-leucyl-L-leucine methyl ester (LeuLeuOMe), which can kill a large variety of cells with bone marrowderived immune cells being the most sensitive (Thiele and Lipsky, 1990;Uchimoto et al, 1999;Droga-Mazovec et al, 2008). This dipeptide ester was shown to accumulate inside lysosomes and acquired detergent properties after polymerization mediated by cathepsin C (Thiele and Lipsky, 1990).…”
Section: Lysosomotropic Agentsmentioning
confidence: 99%
“…However, the best characterized lysosomotropic detergent is L-leucyl-L-leucine methyl ester (LeuLeuOMe), which can kill a large variety of cells with bone marrowderived immune cells being the most sensitive (Thiele and Lipsky, 1990;Uchimoto et al, 1999;Droga-Mazovec et al, 2008). This dipeptide ester was shown to accumulate inside lysosomes and acquired detergent properties after polymerization mediated by cathepsin C (Thiele and Lipsky, 1990). Moreover, the compound showed excellent results in the prevention of graft-versus-host disease in mice and entered clinical studies for allogenic bone marrow transplantation (Filicko-O'Hara et al, 2009), which were, however, discontinued.…”
Section: Lysosomotropic Agentsmentioning
confidence: 99%